Psychological determinants of financial planning for retirement among university employees / Choo Siew Ming - Choo , Siew Ming (2020)
Retirement refers to the post-work period of a person’s life. During this period, individuals cease working, thus affecting their regular source of income. Hence, it is important that individuals plan to cater for the financial requirements during retirement. However, planning is not an easy task as individuals are besieged by a variety of psychological, environmental, financial and life challenges. Current research in this field had been inconclusive and fragmented on the determinants influencing planning behaviours. This research aims to draw on the constructs of the Theory of Planned Behaviour (TPB) to investigate this behaviour, in particular planning financially for retirement. TPB assumes that behaviour can be predicted and explained by using a set of determinants; that is attitudes, subjective norms and perceived behavioural control. Research using TPB’s integrative framework has been positive in many studies but its use in financial and retirement behaviour studies is limited. To investigate the suitability of TPB, a survey is conducted among a sample of university employees in Malaysia. The findings reveal that subjective norms and attitudes influence intentions to plan. Conversely, perceived behavioural control has no influence on intentions. These findings provide empirical support for the use of TPB as a general model of planning for financial retirement in Malaysia. It contributes to the body of knowledge on financial behaviours, by stressing the importance of understanding the motivations of individuals in their choices on financial matters, planning and retirement issues.